Determination of polyphenol contents in Papaver rhoeas L. flowers extracts (soxhlet, maceration), antioxidant and antibacterial evaluation. (2020) - Marsoul, A.; Ijjaali, M.; Oumous, I.; Bennani, B.; Boukir, A.
Abstract: The main objective of this study is to valorize the flowers of poppy ( Papaver rhoeas L.) plant belonging to the family of Papaveraceae, by studying the following parameters resulting from two types of methanolic extraction methods (maceration, soxhlet): polyphenols content, antioxidant power and antibacterial effects. The total phenolic contents (TPC) determined by Folin-Ciocalteu colorimetric assays in both maceration and soxhlet extracts are rich in total phenolic concentrations with the values of 95.4 ± 2.42 and 165.4 ± 3.84 mg GAE/g, respectively, while the flavonoid fractions represent the minor proportion with 8.67 ± 0.024 mgQE/g and 21.7 ± 2.05 mg QE/g, respectively. The antioxidant activity was evaluated using free radical scavenging method diphenyl picryl-hydrazyl (DPPH), the results obtained from both extracts are interesting than that of ascorbic acid used as a standard (IC50 = 0.13879 mg/ml). The highest and important antioxidant power recorded was attributed to soxhlet extract (IC50 = 3.81 mg/ml) compared to that of maceration extract (IC50 = 4.97 mg/ml). The antibacterial activities were conducted in agar medium against six types of bacterial species, half of which are Gram - ( Escherichia coli, Klebsiella pneumonia, Salmonella spp ) and the others are Gram + ( Staphylococcus aureus, Listeria monocytogenes, and Enterobacter feacalis ). The potential antibacterial effect was revealed by soxhlet extract against Enterobacter feacalis, with MIC value of 0.11 mg/ml . All extracts present an interesting bacteriostatic effect on the studied strains and could be used as a natural and alternative to synthetic antibiotic drugs. Finally, the soxhlet extract has proven to be the best procedure for studying the Papaver rhoeas flowers, in terms of polyphenol recovery, antioxidant effect, and antimicrobial activities. Those properties might be explored, as a natural antibacterial with health benefits, and a source of natural antioxidants in food.